2020
DOI: 10.1002/poi3.238
|View full text |Cite
|
Sign up to set email alerts
|

Social Media, Web, and Panel Surveys: Using Non‐Probability Samples in Social and Policy Research

Abstract: The use of online surveys has grown rapidly in social science and policy research, surpassing more established methods. We argue that a better understanding is needed, especially of the strengths and weaknesses of non-probability online surveys, which can be conducted relatively quickly and cheaply. We describe two common approaches to non-probability online surveysriver and panel sampling-and theorize their inherent selection biases: namely, topical selfselection and economic self-selection. We conduct an emp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
175
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(191 citation statements)
references
References 43 publications
1
175
0
15
Order By: Relevance
“…While the survey company recruited the panel on a quota‐controlled basis to be representative of the adult population, our study sample was predominantly female indicating some selection effects. Hence, it is important to work with larger probability‐based samples to build up a full profile of everyday life during the crisis, and the current study should not be seen as a substitute for such work (Lehdonvirta, Oksanen, Räsänen, & Blank, 2020). However, we examine within‐person effects and did not identify evidence that the effects identified differed systematically between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…While the survey company recruited the panel on a quota‐controlled basis to be representative of the adult population, our study sample was predominantly female indicating some selection effects. Hence, it is important to work with larger probability‐based samples to build up a full profile of everyday life during the crisis, and the current study should not be seen as a substitute for such work (Lehdonvirta, Oksanen, Räsänen, & Blank, 2020). However, we examine within‐person effects and did not identify evidence that the effects identified differed systematically between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…A web-based format was chosen over random-digit dialling for both cost considerations and time constraints. Research to date has shown that Internetmediated questionnaires have reliability and internal validity characteristics that are proportionate to traditional formats [44,45]. We adopted the snowball sampling strategy, with its strengths and weaknesses.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The publication, on October 1, 2019, of the list of products on site does not help reassure the public to such an extent that before the end of the first week following the event, the court of Rouen is seized of several complaints, a parliamentary information mission is created, the dissatisfaction of several impacted professions is expressed in various ways. Fire started A fire broke out on Thursday, September 26, 2019 at around 3:40 a.m. within the Lubrizol factory hitting the barrel crushing and storage facilities as well as a nearby warehouse belonging to the company SCMT (Shopping and transport company) 19 . The formal origin of the fire has not been established.…”
Section: September 26 2019 Firementioning
confidence: 99%
“…At the same time, the municipalities concerned, once informed, also initiate their PPI and respectively set up a crisis unit. For the commune of Le Petit-Quevilly, the chronology is as follows 22 : https://www.alternative76.fr/2019/09/26/incendie-de-l-usine-lubrizol-contexte-bilan-et-t%C3%A9moigages/ 18 https://fr.wikipedia.org/wiki/Chronologie de l%27incendie de l%27usine Lubrizol %C3%A0 Rouen and de ses cons%C3% A9quences, (French) 19 Fire at Lubrizol Rouen, France Population alert At 6:11 a.m., the city of Petit-Quevilly uses its SMS and voice call alert system to which residents who wish to subscribe (6,770 households 23 ). Some residents close to the factory got scared from 5:15 a.m. -5:30 a.m. At 7:10 a.m., the Seine-Maritime prefecture announces that it will set off the sirens at 7:45 a.m. to alert the population.…”
Section: Crisis Unitmentioning
confidence: 99%
See 1 more Smart Citation